2013
DOI: 10.1021/ci400241s
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Characteristic Interaction Patterns on Protein–Protein Binding Interfaces

Abstract: Protein-protein interactions are observed in various biological processes. They are important for understanding the underlying molecular mechanisms and can be potential targets for developing small-molecule regulators of such processes. Previous studies suggest that certain residues on protein-protein binding interfaces are "hot spots". As an extension to this concept, we have developed a residue-based method to identify the characteristic interaction patterns (CIPs) on protein-protein binding interfaces, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Therefore, an increase of the general consistency is observed when a compound is analyzed under similar experimental conditions. However, too low SD values, even lower than expected experimental error (SD­(p K i ) = 1 (for details see ref )), might be caused by repeatedly published values, which can be found in the literature, even when references to earlier studies were included (and would have sufficed). Such cases make it difficult to analyze the real activity of compounds and should be taken into account in the process of data mining for drug discovery.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, an increase of the general consistency is observed when a compound is analyzed under similar experimental conditions. However, too low SD values, even lower than expected experimental error (SD­(p K i ) = 1 (for details see ref )), might be caused by repeatedly published values, which can be found in the literature, even when references to earlier studies were included (and would have sufficed). Such cases make it difficult to analyze the real activity of compounds and should be taken into account in the process of data mining for drug discovery.…”
Section: Resultsmentioning
confidence: 95%
“…Many studies are dedicated to the integration of chemical and biological data. Different approaches have been proposed to establish drug–target–disease relationships, identify protein–protein interactions, , interpret associations between proteins and genes, annotate proteins as well as protein expression and disease mechanisms, perform gene ontology analysis, , search for associations between drugs and diseases; and extract data on the melting points of chemical compounds …”
Section: Introductionmentioning
confidence: 99%
“…The triplets for which each edge of the triangles was larger than the maximum range of the edge between corresponding atom pairs in the training set were not considered. Additionally, 7.0 Å (two times the maximum range of hydrogen bonds) was set as the maximum threshold for the atom pairs that were not in the training set. For the retained collections of multi‐source heterogeneous atoms of triplets, a preference factor (Li, Liu, Han, Li, & Wang, ) ( PF ) value was adopted to determine the probability of the presence of water molecules around them. The shape‐matching method was used to match triangles with similar shapes in the training set to the retained collections of multi‐source heterogeneous atoms of triplets. The two ratios and the sum of the lengths of the three edges of the triangle formed by the collection of multi‐source heterogeneous atoms of a triplet were calculated.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The appropriate hydrogen/hydrophobic interactions among proteins are involved in multiple biological processes and other underlying molecular mechanisms in different diseases 39 , 40 . Furthermore, prior research data also showed that the stability of protein complexes depends upon the hydrogen bonds 41 .…”
Section: Molecular Dockingmentioning
confidence: 99%